Dendritic post-cross-linked resin for the adsorption of crystal violet from aqueous solution. (January 2019) - Yuan, Xiaomi; Zhou, Fa; Man, Ruilin; Huang, Jianhan
Highlights: We developed a dendritic post-cross-linked resin with micro/mesoporous structure. The dendritic post-cross-linked resin contains considerable amido, amino, and carboxyl groups. The dendritic post-cross-linked resin is efficient for the adsorption of crystal violet. The dendritic post-cross-linked resin has potential application in adsorptive removal of organic dyes. Abstract: Herein we adopted methyl acrylate (MA) as the functional monomer and divinylbenzene (DVB) as the cross-linking agent, and performed the polymerization, Friedel-Crafts reaction, ammonolysis reaction, and acylation reaction, and hence developed a kind of dendritic post-cross-linked resin namely HCPDTa. The results indicate that HCPDTa is a microporous and mesoporous material with the Brunauer-Emmett-Teller (BET) surface area ( SBET ) of 599 m 2 ∙g −1 and pore volume ( Vtotal ) of 0.65 cm 3 ∙g −1, respectively, and it contains considerable amido, amino, and carboxyl groups on the dendritic structure. HCPDTa is employed to adsorb crystal violet from aqueous solution and it reveals that HCPDTa is effective for the adsorption, the maximum adsorption capacity ( qm ) reaches 497.5 mg∙g −1 at 298 K, 40 min is sufficient for adsorption reaching equilibrium, and the resin can be regenerated easily and repeatedly used. The synthetic strategy in this study can provide a new idea for the synthesis of some other dendritic materials, and the developed dendritic post-cross-linked resins have potential application in adsorptive removal of organic dyes.